2010
DOI: 10.1007/s10900-010-9283-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus (HBV) Infection Among Hmong Immigrants in the San Joaquin Valley

Abstract: Chronic hepatitis B infection (HBV) is the major cause of primary liver cancer worldwide and Asians are disproportionately affected. The prevalence of HBV among most Asian American groups has been well documented, except in Hmong immigrants in the United States. The aim of this study was to determine the prevalence of HBV among Hmong immigrants in the San Joaquin Valley of California. A convenient sample of 534 Hmong age ≥18 years was recruited at various locations throughout Fresno County. Blood samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
16
3
Order By: Relevance
“…The prevalence in Chinese immigrants grouped by province/region of birth is similar to that found in China with the exception of the Fujian province (7, 8, 10). The prevalence of chronic HBV in Fujianese immigrants in our study was more than twice the rate (17.1%) reported for the Fujian province in the China National Survey, the province with the highest HBV infection prevalence in China (7, 11, 25, 26). Higher infection rates among the Fujianese in our sample may be due to specific migration-related factors that overlap with HBV risk factors.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The prevalence in Chinese immigrants grouped by province/region of birth is similar to that found in China with the exception of the Fujian province (7, 8, 10). The prevalence of chronic HBV in Fujianese immigrants in our study was more than twice the rate (17.1%) reported for the Fujian province in the China National Survey, the province with the highest HBV infection prevalence in China (7, 11, 25, 26). Higher infection rates among the Fujianese in our sample may be due to specific migration-related factors that overlap with HBV risk factors.…”
Section: Discussioncontrasting
confidence: 43%
“…While less than 0.5% of the US population tests positive for HBsAg, the prevalence of chronic HBV infection among Asian Americans is estimated to be between 9 and 15%, and may be as high as 25% in select subgroups of recent immigrants (20-26). Asian Americans, the fastest growing racial/ethnic group in the US, are largely foreign-born (27) and account for 60% of persons in the US with chronic HBV (28).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study among Hmong living in the San Joaquin Valley found almost 17% prevalence of CHB, and high-risk behavior including multiple sex partners, tattooing, and injecting drugs are common within the community. 30 These refugee groups could benefit from early screening for HBV infections, identification, and treatment upon their arrival, which can prevent further progression of disease to end-stage liver disease and HCC, and diminish the risk of transmitting HBV to their contacts.…”
Section: Discussionmentioning
confidence: 99%
“…The Central Valley has a diverse ethnic population composition, about 30% to 68% Hispanics and 3% to 14% Asians across various counties. Our recent prospective study revealed that approximately one out of every six Hmong immigrants in the Central California Valley is infected with HBV 22. Therefore; the disparities in prevalence of viral hepatitis are expected in the valley as compared to general US population.…”
Section: Introductionmentioning
confidence: 95%